2011
DOI: 10.1292/jvms.10-0311
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylnitrosamine-Induced Liver Fibrosis and Recovery in NOD/SCID Mice

Abstract: ABSTRACT. There is a need for a new liver fibrosis model of immunodeficient mice to study the effects of cell therapy on liver disease because there are not many animal models available to study the effects of cell therapy. In this study, we induced liver fibrosis using dimethylnitrosamine (DMN) in NOD/SCID mice to create an animal model for liver disease. DMN (5 mg/kg, i.p.) was injected intraperitoneally for three consecutive days per week for 6 or 8 weeks, and the mice were sacrificed at weeks 0, 4 and 8 af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(28 reference statements)
0
4
0
1
Order By: Relevance
“…In a comparative model, Hobbie et al (2011) reported that Japanese medaka fish ( Oryzias latipes ) exposed to DMN developed morphological hepatic changes similar to those observed in human fibrotic livers and the well-established DMN-induced rat model of hepatic fibrosis (Ala-Kokko et al, 1987; Jezequel et al, 1987; Ohara et al, 2007; Hobbie et al, 2011; Hyon et al, 2011). Currently, knowledge of the mechanisms of hepatic fibrosis and progression to neoplasia in fish is limited.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a comparative model, Hobbie et al (2011) reported that Japanese medaka fish ( Oryzias latipes ) exposed to DMN developed morphological hepatic changes similar to those observed in human fibrotic livers and the well-established DMN-induced rat model of hepatic fibrosis (Ala-Kokko et al, 1987; Jezequel et al, 1987; Ohara et al, 2007; Hobbie et al, 2011; Hyon et al, 2011). Currently, knowledge of the mechanisms of hepatic fibrosis and progression to neoplasia in fish is limited.…”
Section: Introductionmentioning
confidence: 85%
“…Dimethynitrosamine (DMN) is a potent carcinogenic hepatotoxin previously used in rodents to model human hepatic fibrosis, cirrhosis, and HCC (Ala-Kokko et al 1987; Jezequel et al 1987; George et al 2001; Tada et al 2001; Hyon et al 2011). In a comparative model, Hobbie et al (2011) reported that Japanese medaka fish ( Oryzias latipes ) exposed to DMN developed morphological hepatic changes similar to those observed in human fibrotic livers and the well-established DMN-induced rat model of hepatic fibrosis (Ala-Kokko et al 1987; Jezequel et al 1987; Ohara et al 2007; Hobbie et al 2011; Hyon et al 2011). Currently, knowledge of the mechanisms of hepatic fibrosis and progression to neoplasia in fish is limited.…”
Section: Introductionmentioning
confidence: 99%
“…This is of prime importance in order to achieve adequate experimental observations in immunodeficient animals with liver fibrosis, for example in hepatocellular carcinoma models. Indeed, high mortality rate was consistently observed in a dimethylnitrosamine (DMN) model using NOD-SCID mice and also in a Foxn1 nu/nu mice model using IP injections of TAA [27, 33]. In the present study, using step-wise increased dosage of TAA and a more continuous delivery through drinking water, toxicity of TAA was reduced without undermining the extent of its fibrogenic impact.…”
Section: Discussionmentioning
confidence: 53%
“…Recently, Hyon et al . showed that liver fibrosis in NOD-SCID mice (lacking both T and B cells) also needed a longer treatment period to reach adequate degrees of fibrosis [33]. Since both the delivery method and genetic background of the animals differed, we cannot conclude as to why Foxn1 nu/nu mice took longer to achieve similar level of fibrosis; however, the less aggressive TAA regimen is likely to influence the development of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Em um primeiro momento, optamos por estabelecer um modelo experimental baseado naquele desenvolvido por Ozawa e colaboradores (Ozawa et al, 2006) . Também tratados com três injeções ip consecutivas por semana de DMN 10 µg/g, porém durante quatro semanas, os níveis séricos de ALT, AST, FA e BT de ratos Sprague-Dawley aumentaram com o tempo de tratamento com DMN (Saha et al, 2007) (Hyon et al, 2011;Ying et al, 1980). (Ozawa et al, 2006), histológicas (Choi et al, 2010;Yue et al, 2010) e aumento dos níveis séricos de FA (Shin et al, 2010) observados na literatura, mas a hepatectomia não parece contribuir para o agravamento das lesões.…”
Section: -Padronização Do Modelo Animal De Injúria Hepática Induzida unclassified